Coastal state jurisdiction to protect and preserve the marine environment: evolution and development of the LOSC regime - Testa, David (2019)
This thesis examines the potential impact of evolution and development of the 1982 United Nations Convention on the Law of the Sea (LOSC) on coastal State jurisdiction to protect and preserve the marine environment against accidental vessel-source pollution in the Exclusive Economic Zone (EEZ) and in international straits.